An investigation of physicochemical properties of Nigella sativa L. Seed oil from Al-Qassim by different extraction methods - Moneer Alrashidi; Darfizzi Derawi; Jumat Salimon; Mohamad Firdaus Yusoff (Journal of King Saud University: Science, 2020)
An investigation of physicochemical properties of Nigella sativa seed oil from Al-Qassim, KSA was conducted using cold press and Soxhlet extraction methods. The effect of solvent polarity on the oil components and properties were examined using hexane, tetrahydrofuran, ethanol, dichloromethane, methanol and methanol-water binary system. The results demonstrated a high yield of oil with the Soxhlet method using ethanol (40.16%) while the samples extracted with the methanol–water binary system produced the lowest yield (28.28%). Linoleic acid was the major free fatty acid in all samples followed by oleic and palmitic acids. Moreover, the triacylglycerol analysis was carried out using a high-performance liquid chromatography system. The results revealed that the studied oil samples were rich in unsaturated triacylglycerols mostly as 3 Linoleic acid (LLL) but low in saturated triacylglycerols. Thymoquinone, which is known as a powerful antioxidative and antiradical agent was detected in all samples except the sample extracted with the methanol–water binary system. The effect of solvent polarity and the solvent boiling point was observed through the quantity of the main components of each oil sample even though they are from the same source of seed. This study showed that the aforementioned properties were affected by the polarity of the solvent used during the extraction process.